EBG-backed ultrawideband circularly polarized Archimedean spiral antenna scheme for IoT applications - Bancha Luadang; Chalanthon Ainthachot; Pisit Janpangngern; Khanet Pookkapund; Danai Torrungrueng; Monai Krairiksh; Chuwong Phongcharoenpanich (My University, 2025)
This research proposes a low-profile ultrawideband circularly polarized Archimedean spiral antenna with an electromagnetic band gap (EBG)-backed structure. The proposed antenna scheme consists of an upper-layer spiral radiator, a microstrip tapered balun, and a lower-layer high-impedance circular EBG reflector of three concentric rings of trapezoid-shaped unit cells. The antenna scheme can achieve a significant profile reduction, with a total height of 0.1 wavelengths at the lowest operational frequency. The integration of the EBG reflector improves the radiation characteristics and antenna gain, achieving a maximum gain of 9.87 dBic at 6.90 GHz. The EBG reflector also improves impedance matching and axial ratio (AR) over the 1.5-8.75 GHz frequency range, achieving a wide AR bandwidth of 141.46%. The novelty of this work lies in the integration of Archimedean spiral antenna with high-impedance EBG reflector of trapezoid-shaped unit cells to enhance the impedance and AR bandwidths without increasing the overall antenna profile. Essentially, the proposed antenna scheme is suitable for broadband communication systems that require ultrawide bandwidth, circular polarization, and a small form factor.
Keywords: Spiral antenna; Antenna Design and Analysis